Modern Islamic banking : products, processes in practice - Schoon, Natalie (Chichester, West Sussex : John Wiley & Son, 2016)
'A complete, detailed guide to modern Islamic banking fundamentals Modern Islamic Bankingprovides a comprehensive, up-to-the-minute guide to the products, processes and legal doctrines underlying Islamic banking. Written by a pioneering practitioner in the field, this book provides thorough guidance and expert-level perspective on the principles and applications of this alternative-banking model. You'll begin by learning the fundamentals, vocabulary and key concepts of Islamic banking, then explore key products including istisna'a, murabaha, musharaka, ijara, sukuk, and salam. Coverage then moves into practical applications of Islamic products to a variety of contexts including asset management, treasury, risk management, venture capital, SME finance, micro-finance and taxation. Regulatory frameworks are discussed in detail, including extensive coverage of post-financial crisis Islamic bank valuation. Islamic banking has experienced rapid growth over the past decade, a trend that is set to continue given the sector's successful weathering of the financial crisis. This book brings you up to speed on this alternative way of banking, and shows you how it applies within your own current practices. Understand the principles of Islamic banking and finance Learn the products, vocabulary and key concepts of the field Consider the applications in a variety of financial contexts Explore the regulatory frameworks and valuation of Islamic banks Islamic banking practices differ from Western banking in fundamental ways -- it's these differences that shielded the sector during the global crisis, but they also require practitioners to understand a whole new set of rules, products and practices. Modern Islamic Banking gives you a solid understanding of the fundamentals and expert insight into modern practical applications'--
Machine generated contents note: Acknowledgments About the Author Introduction Chapter 1: Historic Developments 1.1 The History of Finance 1.2 The History of Islamic Finance Chapter 2: Economic Principles 2.1 Early Economic Thought 2.2 The Prohibition of Interest 2.3 Modern Economics and Banking 2.4 Islamic Ethics 2.5 Contracts and Prohibitions 2.6 Sharia'a and Prohibitions Chapter 3: Islamic Finance Products Explained 3.1 Definitions 3.2 The Asset 3.3 Transaction Types 3.4 Bond-Like Instruments Chapter 4: Distribution of Islamic Products 4.1 Distribution Channels and Sharia'a Compliance 4.2 Sharia'a Compliant versus Sharia'a Based 4.3 Competition or Opportunity Chapter 5: Application of Islamic Products in Retail Finance 5.1 Current Accounts 5.2 Credit card 5.3 Deposit Accounts 5.4 Funds 5.5 Mortgage Products 5.6 Personal Loans 5.7 Transfers Chapter 6: Application of Islamic Products in Treasury 6.1 Interbank Liquidity 6.2 Hedging 6.3 Combination of Transaction Types 6.4 Asset-Based Securities 6.5 Syndication Chapter 7: Application of Islamic Products in Corporate Finance 7.1 Trade Finance 7.2 Project Finance 7.3 Property Finance 7.4 Leasing Chapter 8: The Application of Islamic Products to Private Equity Chapter 9: The Role of the London Metal Exchange 9.1 The London Metal Exchange 9.2 Warrants 9.3 LME Base Metals Chapter 10: Asset Management 10.1 Selection of Sharia'a compliant investments 10.2 Types of Funds Chapter 11: Risks in Islamic Banks Chapter 12: Governance 12.1 Roles 12.2 Social Responsibilities 12.3 Structures and variations of Sharia'a Supervisory Boards 12.4 Serving on Multiple Boards Chapter 13: The Islamic Financial Infrastructure 13.1 Regulatory Institutions 13.2 Socially Responsible Investments and Micro Finance 13.3 The Case for LIBOR Chapter 14: Capital Adequacy Concerns 14.1 Challenges Within the Basel Capital Adequacy Framework 14.2 IFSB Capital Adequacy Standards 14.3 Capital Adequacy for Islamic Banks around the World 14.4 Expected Future Developments in Capital Adequacy Chapter 15: How to Value a Bank 15.1 The Components 15.2 The Models 15.3 The Special Case of Banks 15.4 The Special Case of Islamic Banks 15.5 Can a Bank be Valued? Chapter 16: The Future Glossary Selected Bibliography Index .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Banks and banking -- Islamic countries; Banks and banking -- Religious aspects -- Islam; Finance -- Islamic countries; Finance -- Religious aspects -- Islam; Banks and banking; Banks and banking -- Religious aspects -- Islam; Finance; Finance -- Religious aspects -- Islam; BUSINESS & ECONOMICS / Finance; Islamic countries; Electronic books